MO273: Water Restriction and Age Increase the Risk of Triple Whammy-Induced Acute Kidney Injury. (3rd May 2022) - María Baranda Alonso, Eva; Fuentes-Calvo, Isabel; Sancho Martinez, Sandra M; Diaz-Morales, Noelia; Hidalgo-Thomas, Omar; Misol-Ortiz, Andrea; Lopez-Hernandez, Francisco J; Martinez Salgado, Carlos
Abstract: BACKGROUND AND AIMS: Hypertension has a high prevalence in adult population and represents an important cause of premature death worldwide. Its treatment often consists of the combination of several antihypertensive drugs, including angiotensin-converting-enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARB) and diuretics. Hypertensive patients eventually receive analgesic treatments linked to other pathologies. The combination of antihypertensive treatments (ACEi/ARB and diuretics) with non-steroidal anti-inflammatory drugs (NSAIDs) may generate an acute kidney injury (AKI) due to a reduction in the glomerular filtration rate. According to different studies, the incidence of AKI following this triple therapy or Triple Whammy (TW) ranges from < 1% to up to 22%. This suggests that additional factors determine the renal impact of the TW. Because the incidence of TW-induced AKI is higher among older adults, and because the prevalence of dehydration is especially elevated among them, the aim of our study was to model in rats the influence of water restriction and ageing on the renal effect of the TW. METHOD: Male Spontaneously Hypertensive Rats (SHR) of 3 and 7 months of age were divided in four experimental groups: control group (CT), control group with 60%–70% water restriction of basal intake (i.e. 15 mL/day) (CT-WR), TW group (TW), and TW group with 60%–70% water restriction of basal intake (i.e. 15 mL/day) (TW-WR). Both TW groups received antihypertensive treatment with Trandolapril in drinking water and Furosemide i.p. for 4 days, and then a triple therapy for 2 days with Trandolapril and Ibuprofen in drinking water and Furosemide i.p. Urine and blood samples were collected at basal state (B), after 4 days of the combined treatment of Trandolapril + Furosemide (day 4) and two days after adding ibuprofen treatment (day 6). Blood pressure was measured on B and day 4, and the kidneys were removed at the end of the experiment. We analyzed the hydration status (water balance), the renal function (plasma creatinine and urea determination) and renal histological alterations (hematoxylin–eosin staining). RESULTS: Antihypertensive treatment decreased systolic blood pressure in the TW and TW-WR groups, and did not induce any effects in CT and CT-WR groups. Water balance was lower in CT-WR, TW and TW-WR groups than in CT group, which may indicate partial dehydration, being this balance negative in TW-WR group. No differences in creatinine and plasma urea levels were found on day 6 between 3- and 7-months-old rats in TW group. An experimental AKI was observed in rats treated with TW and water restriction, characterized by increased creatinine and plasma urea; this experimental AKI was more severe in 7-month-old rats. CT and CT-WR groups showed normal renal function. There were no histological alterations in any of the experimental groups. CONCLUSION: Water restriction is an important risk factor in the development of AKI in TW therapy, and although age differences do not have a relevant effect on their own, the combination of age and water restriction increases the risk.